Sapling performance along resource gradients drives tree species distributions within and across tropical forests. Issue 9 (1st September 2014) - Sterck, F.; Markesteijn, L.; Toledo, M.; Schieving, F.; Poorter, L.
Abstract : Niche differentiation is a major hypothesized determinant of species distributions, but its practical importance is heavily debated and its underlying mechanisms are poorly understood. Trait‐based approaches have been used to infer niche differentiation and predict species distributions. For understanding underlying mechanisms, individual traits should be scaled up to whole‐plant performance, which has rarely been done. We measured seven key traits that are important for carbon and water balance for 37 tropical tree species. We used a process‐based plant physiological model to simulate the carbon budget of saplings along gradients of light and water availability, and quantified the performance of the species in terms of their light compensation points (a proxy for shade tolerance), water compensation points (proxy for drought tolerance), and maximum carbon gain rates (proxy for potential growth rate). We linked species performances to their observed distributions (the realized niches) at two spatial scales in Bolivian lowland forests: along a canopy openness gradient at local scale (∼1 km 2 ) and along a rainfall gradient (1100–2200 mm/yr) at regional (∼1000 km) scale. We show that the water compensation point was the best predictor of species distributions along water and light resource gradients within and across tropical forests. A sensitivity analysis suggests that the stomatal regulation of minimum leaf water potentials, rather than stem hydraulic traits (sapwood area and specific conductivity), contributed to the species differences in the water compensation point of saplings. The light compensation point and maximum carbon gain, both driven by leaf area index and leaf nitrogen concentration, also contributed to differential species distributions at the local scale, but not or only marginally at the regional scale. Trait‐and‐physiology‐based simulations of whole‐plant performance thus help to evaluate the possible roles of individual traits in physiological processes underlying species performance along environmental gradients. The development of such whole‐plant concepts will improve our ability to understand responses of plant communities to shifts in resource availability and stress under global change.